Evaluating the effects of curcumin nanomicelles on clinical outcome and cellular immune responses in critically ill sepsis patients: A randomized, double-blind, and placebo-controlled trial - Karimi, Arash; Pourreza, Sanaz; Vajdi, Mahdi; Mahmoodpoor, Ata; Sanaie, Sarvin; Karimi, Mozhde; Tarighat-Esfanjani, Ali (Frontiers in Nutrition, 2022)
In sepsis, the immune system is overreacting to infection, leading to organ dysfunction and death. The purpose of this study was to investigate the impacts of curcumin nanomicelles on clinical outcomes and cellular immune responses in critically ill sepsis patients. For 10 days, 40 patients in the intensive care units (ICU) were randomized between the nano curcumin (NC) and placebo groups in a randomized study. We evaluated serum levels of biochemical factors, inflammatory biomarkers, the mRNA expression levels of FOXP3, NLRP-3, IFN-γ, and NF-kβ genes in the PBMCs, and clinical outcomes before the beginning of the supplementation and on days 5 and 10. NLRP3, IFN-γ, and NF-kβ mRNA expression levels significantly P=0.014, P=0.014, and P=0.019, respectively) decreased, but FOXP3 mRNA expression levels increased significantly (P=0.008) in the NC group, compared to the placebo group after 10 days. NC supplementation decreased serum levels of IL-22, IL-17, and HMGB-1(P<0.05). Nevertheless, biochemical factors and nutritional status did not differ significantly (P>0.05). NC supplementation resulted in decreased sequential organ failure assessment and multiple organ dysfunction syndromes score, while it did not have significant impacts on length of stay in the ICU, systolic blood pressure, diastolic blood pressure, a saturation of oxygen (%), and respiratory rate (breaths/min) PaO2/FiO2 (p>0.05). For critically ill patients with sepsis, NC supplementation may be an effective therapeutic strategy. To achieve the best results, more randomized clinical trials involving longer follow-up periods and different doses are needed.